Antifungal Activity of Jasminum sambac against Malassezia sp. and Non-Malassezia sp. Isolated from Human Skin Samples. (10th November 2014) - Santhanam, Jacinta; Abd Ghani, Farhana Nadiah; Basri, Dayang Fredalina
Abstract : Malassezia sp. causes skin diseases such as pityriasis versicolor, folliculitis, and atopic dermatitis. The present study aims to evaluate the antifungal activity of J. sambac or Arabian jasmine, a flowering plant abundant in the Southeast Asia against Malassezia sp. using disc diffusion and broth microdilution method. The methanol extract and essential oil from the flowers and leaves of J. sambac were, respectively, prepared using solvent extraction and hydrodistillation process. Skin samples from individuals with dandruff were cultured on Sabouraud dextrose agar overlaid with olive oil. The fungi that grew were observed microscopically, tested with Tween assimilation test, and cultured on CHROMagar (the chromogenic media pioneer) to identify Malassezia sp. Out of 5 skin samples, only 2 Malassezia sp. isolates were identified based on morphology and their ability to assimilate Tween. The inhibition zones of methanol extract of flowers and leaves of J. sambac and essential oil of flowers showed potential for antifungal activity with inhibition zones of 11.10 ± 1.92, 12.90 ± 1.68, and 13.06 ± 0.26 mm, respectively, and minimum inhibitory concentration (MIC) values of 80 mg/mL to 160 mg/mL and 50%, respectively. In conclusion, J. sambac may be used as an alternative treatment against Malassezia -associated skin infections.